Preoperative homocysteine modifies the association between postoperative C-reactive protein and postoperative delirium - Ma, Xin; Mei, Xinchun; Tang, Tianyi; Wang, Meijuan; Wei, Xiaoyi; Zheng, Hailin; Cao, Jing; Zheng, Hui; Cody, Kathryn; Xiong, Lize; Marcantonio, Edward R.; Xie, Zhongcong; et al. (Frontiers in Aging Neuroscience, 2022)
Background: Homocysteine and C-reactive protein (CRP) may serve as biomarkers of postoperative delirium. We set out to compare the role of blood concentration of homocysteine versus CRP in predicting postoperative delirium in patients. Methods: In this prospective observational cohort study, the plasma concentration of preoperative homocysteine and postoperative CRP was measured. Delirium incidence and severity within three days postoperatively were determined using the Confusion Assessment Method and Confusion Assessment Method-Severity algorithm. Results: Of 143 participants (69% female, median [interquartile range, 25th-75th] age of 71 [67-76] years) who had knee or hip surgery under general anesthesia, 44 (31%) participants developed postoperative delirium. Postoperative plasma concentration of CRP was associated with postoperative delirium incidence (adjusted odds ratio [OR] per one standard deviation change in CRP: 1.51; 95% Confidence Interval [CI]: 1.05, 2.16; P = 0.026), and severity (in which each one standard deviation increase in postoperative CRP was associated with a 0.47 point (95% CI: 0.18-0.76) increase in the severity of delirium, P = 0.002) after adjusting age, sex, preoperative Mini-Mental State Examination score and the days when postoperative CRP was measured. A statistically significant interaction (adjusted P = 0.044) was also observed, in which the association between postoperative plasma concentration of CRP and postoperative delirium incidence was stronger in the participants with lower preoperative plasma concentrations of homocysteine compared to those with higher preoperative levels. Conclusion: Pending validation studies, these data suggest that preoperative plasma concentration of homocysteine modifies the established association between postoperative plasma concentration of CRP and postoperative delirium incidence.